The Effect Of Array Spacing And The Influence Of The Radiation Pattern Of The Element In A Pattern Synthesis Of Uniform Circular Arrays - Suárez Fajardo, Carlos Arturo; Ferrando Bataller, Miguel; Valero Nogueira, Alejandro; Forero, Jairo Antonio (Ingeniería, 2002)
In this article, the effect of array spacing and the influence of the radiation pattern of the element have been considered in the synthesized radiation pattern using circular arrays of directive elements uniformly arranged.